2010
DOI: 10.3390/cancers2031705
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Crypt Foci: The Case for Inclusion as a Biomarker for Colon Cancer

Abstract: Aberrant crypt foci (ACF) are one of the earliest histopathological manifestations of colon cancer. In this review, we critically present the molecular, cellular, histopathological, and chemopreventive evidence that ACF are relevant biomarkers for colon cancer. The laboratory and clinical evidence are highly suggestive that ACF are in the pathway leading to colon cancer, but not all ACF will do so. The possible fate and outcome of ACF in the progression toward colon cancer may be dependent on a number of featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 64 publications
3
27
0
1
Order By: Relevance
“…However, a few years later, the same author suggested and others confirmed that AFC in fact was part of the sequential evolution of colon carcinogenesis, which can become dysplastic, which can give rise to adenomas and colorectal carcinoma in that order, serving then as a model of early lesions, that is, pre-neoplastic lesions in colorectal carcinogenesis 20,21 .…”
Section: Discussionmentioning
confidence: 98%
“…However, a few years later, the same author suggested and others confirmed that AFC in fact was part of the sequential evolution of colon carcinogenesis, which can become dysplastic, which can give rise to adenomas and colorectal carcinoma in that order, serving then as a model of early lesions, that is, pre-neoplastic lesions in colorectal carcinogenesis 20,21 .…”
Section: Discussionmentioning
confidence: 98%
“…Data with respect to ACF formation partly support this conjecture; however, the effects of nCDase were intermediate: nCDase ‐/‐ mice had 50% fewer ACFs, suggesting a role for nCDase early in tumor initiation. However, the proposed role of ACFs as an early mediator of adenocarcinoma development in the AOM model is disputed (43, 58). Second, the significance of deletion of nCDase in colon cancer development, but not for normal intestine and colon development, suggests that oncogenically transformed cells become “addicted” to the action of nCDase.…”
Section: Discussionmentioning
confidence: 99%
“…size and number of ACF and the severity of colon cancer (Alrawi et al, 2006;Gupta and Schoen, 2009;Wargovich et al, 2010). It has been reported that HLF may induce apoptosis and reduce cancer volume in experimentally induced colon cancer in the nude mouse (Chen et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The size and number of ACF increase as the cancer progresses, so they provide information about the stage of the cancer. There is a positive correlation between the incidence of ACF and cancer severity (Alrawi et al, 2006;Gupta and Schoen, 2008;Wargovich et al, 2010). Treatment outcomes may be evaluated according to the number, size and multicrypt features of ACF (Raju, 2008).…”
Section: Introductionmentioning
confidence: 99%